Animal modeling for myopia - Zheng, Lingman; Liao, Zhiyong; Zou, Jian (Advances in ophthalmology practice and research, 2024)
Myopia is one of the most common eye diseases globally, and has become an increasingly serious health concern among adolescents. Understanding the factors contributing to the onset of myopia and the strategies to slow its progression is critical to reducing its prevalence. Animal models are key to understanding of the etiology of human diseases. Various experimental animal models have been developed to mimic human myopia, including chickens, rhesus monkeys, marmosets, mice, tree shrews, guinea pigs and zebrafish. Studies using these animal models have provided evidences and perspectives on the regulation of eye growth and refractive development. This review summarizes the characteristics of these models, the induction methods, common indicators of myopia in animal models, and recent findings on the pathogenic mechanism of myopia. Investigations using experimental animal models have provided valuable information and insights into the pathogenic mechanisms of human myopia and its treatment strategies.